EXAMINING THE TREND OF INNOVATIVE WORK BEHAVIOUR LITERATURE: A BIBLIOMETRIC ANALYSIS - Abdul Aziz, Hafsah; Ali, Kalsom (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The concept of innovative work behaviour (IWB) has received attention as a strategy to be competitive for an organisation. Given the intricate nature of the global landscape, the emergence of new risks, and the need to enhance organisational resilience in times of crisis, the significance of IWB becomes pertinent, particularly for the public sector. This paper examines the development and the current trends of IWB research from the perspectives of bibliometric indicators. This study retrieved a total of 1,574 documents from the Scopus database between the years 1963 and 2023. The analysis of this study used several tools – Microsoft Excel, VOSviewer, and Harzing's Publish or Perish. The findings of this study show the increasing trends over the last ten years in various disciplines. Research results indicate that IWB research mostly appears in the subject areas of Business, Management, Accounting, Social Sciences, Psychology, Economics and Finance. This study also reveals that China, the United States, Pakistan, Indonesia, and Malaysia have become the five major countries that have created collaborative IWB research. In light of this, the results of this investigation furnish crucial data for advancing IWB research in the realm of multidisciplinary studies.